2016
DOI: 10.1111/2041-210x.12645
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of fine‐scale species distribution models to locational uncertainty in occurrence data across multiple sample sizes

Abstract: Summary1. To generate realistic predictions, species distribution models require the accurate coregistration of occurrence data with environmental variables. There is a common assumption that species occurrence data are accurately georeferenced; however, this is often not the case. This study investigates whether locational uncertainty and sample size affect the performance and interpretation of fine-scale species distribution models. 2. This study evaluated the effects of locational uncertainty across multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 55 publications
3
64
0
4
Order By: Relevance
“…Model transfers can be further hampered by imperfect detectability, spatial and temporal biases in data collection, insufficient sample sizes, the omission of known drivers, or the use of proxy variables [27]. Additionally, species' characteristics such as range size can impact positional accuracy, leading to erroneous predictions if analyses are conducted at scales corresponding with those of the original locational errors [28]. The magnitude of these effects is ultimately unclear, and data quality therefore represents a substantial source of uncertainty [29].…”
Section: Why Transfer Models In the First Place?mentioning
confidence: 99%
“…Model transfers can be further hampered by imperfect detectability, spatial and temporal biases in data collection, insufficient sample sizes, the omission of known drivers, or the use of proxy variables [27]. Additionally, species' characteristics such as range size can impact positional accuracy, leading to erroneous predictions if analyses are conducted at scales corresponding with those of the original locational errors [28]. The magnitude of these effects is ultimately unclear, and data quality therefore represents a substantial source of uncertainty [29].…”
Section: Why Transfer Models In the First Place?mentioning
confidence: 99%
“…MaxEnt; Phillips et al 2006. Use of misrepresentative environmental data, such as that resulting from positional error (Osborne & Leitão 2009, Mitchell et al 2017 or temporal mismatches be tween species and environmental sampling dates (Roubicek et al 2010), is known to reduce SDM performance. Osborne & Leitão (2009) hypothesised that, with positional errors, spatial autocorrelation of environmental data may mitigate substantial mismatch errors between occurrence and environment.…”
Section: Sdms In 3d Marine Environmentsmentioning
confidence: 99%
“…Ideally, environmental data associated with a species occurrence should be collected at the time and place of sampling to avoid spatial (Osborne & Leitão 2009, Mitchell et al 2017 or temporal (Roubicek et al 2010) mismatches between a confirmed presence and associated environmental data. Doing so is not, however, always practical.…”
Section: Quantity−quality Trade-offsmentioning
confidence: 99%
“…inaccurate location of species occurrences) is minimal or mainly associated with relatively older datasets that are often georeferenced from textual descriptions of their locations (which may cause errors of up to hundreds of meters, Wieczorek et al 2004). Additionally, where the marine environment is concerned, species data are often acquired using underwater cameras, in which case the positional error can be affected for example by the camera depth; the deeper the camera is, the greater is the positional error (Rattray et al 2014, Mitchell et al 2017. The positional error of GNSS data may be caused by the use of outdated technology, by poor satellite signal reception (e.g.…”
Section: Introductionmentioning
confidence: 99%